A Low cost automatic cooking oil vending machine for small scale traders - Koi, G. A. (Strathmore University, 2024)
People are always looking for convenience in handling commodities and other basic needs in life and vending machines have played a vital role in making human life easier. However, due to the nature and design of vending machines, they are either too expensive or too large to meet a small-scale trader’s needs. Most small-scale sellers have limited resources and small spaces for operation, introducing the vending machines present in the market would be very costly and will occupy a lot of space leaving them with limited or no space to operate in. Therefore, small-scale traders remain comfortable with the old ways of manually measuring liquids, in this case the cooking oil, as the new technology in liquid dispensing does not cater to their needs. In this study, a low cost automatic cooking oil vending machine that allows the desired amount of oil to be dispensed was fabricated. Though there are some earlier versions of these machines available, this study focused on providing a low cost, simple design that could be easily accessed by small scale traders. This enables easy and accurate measurement in the selling of cooking oil eliminated physical measuring. It is a cheap and efficient way of selling cooking oil, simple and specific to a local seller. The main objective of the study was to develop a low cost automatic cooking oil vending machine for small scale traders. This encompassed looking into existing technologies used by automatic vending machines and the limitations of the current vending machines for small scale traders. The researcher went ahead to design, develop and test the cooking oil vending machine for small scale traders. The study employed a descriptive research design. The various identified features formed the basis for crafting the system tests for the final developed system. An Agile Software development methodology was also employed and the system underwent four main phases: Designing, Development, Testing and Deployment. Key Words: Arduino-Uno microcontroller, Small scale traders, Vending machines, Cooking oil.
Full - text thesis